2011
DOI: 10.1111/j.1745-4549.2011.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Red Pepper on Heterocyclic Aromatic Amines in Fried Beef Longissimus Dorsi Muscle

Abstract: The objective of this study was to investigate the effect of red pepper on formation of heterocyclic aromatic amines (HCAs) in beef chops fried at different temperatures (175, 200 and 225C). Red pepper was added at the rate of 1% (w/w) to the surface of meat before frying. The fried chops were analyzed for five HCAs, including 2‐amino‐3‐methylimidazo[4,5‐f]quinoline (IQ), 2‐amino‐3,4‐dimethylimidazo[4,5‐f]quinoline (MeIQ), 2‐amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline, 2‐amino‐3,4,8‐trimethylimidazo[4,5‐f]quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 53 publications
4
53
1
Order By: Relevance
“…LOQ values were: IQx ¼ 0.013 ng g À1 , IQ ¼ 0.029 ng g À1 , MeIQx ¼ 0.081 ng g À1 , MeIQ ¼ 0.047 ng g À1 , 7,8-DiMeIQx ¼ 0.018 ng g À1 , 4,8-DiMeIQx ¼ 0.025 ng g À1 , PhIP ¼ 0.085 ng g À1 , AaC ¼ 0.039 ng g À1 , and MeAaC ¼ 0.035 ng g À1 . These values are comparable with those in the related literature (Messner & Murkovic, 2004;Oz, 2011;Oz et al, 2015;Oz & Kaya, 2011c;Pais et al, 1999;Skog et al, 1998).…”
Section: Ph Valuesupporting
confidence: 93%
See 2 more Smart Citations
“…LOQ values were: IQx ¼ 0.013 ng g À1 , IQ ¼ 0.029 ng g À1 , MeIQx ¼ 0.081 ng g À1 , MeIQ ¼ 0.047 ng g À1 , 7,8-DiMeIQx ¼ 0.018 ng g À1 , 4,8-DiMeIQx ¼ 0.025 ng g À1 , PhIP ¼ 0.085 ng g À1 , AaC ¼ 0.039 ng g À1 , and MeAaC ¼ 0.035 ng g À1 . These values are comparable with those in the related literature (Messner & Murkovic, 2004;Oz, 2011;Oz et al, 2015;Oz & Kaya, 2011c;Pais et al, 1999;Skog et al, 1998).…”
Section: Ph Valuesupporting
confidence: 93%
“…Similar results for raw beef meat were reported in the literature (Oz & Kaya, 2011b, 2011c. Oz and Kaya (2011c) found that water, total lipid contents and pH values of raw beef chops were at the rate of 74.69e75.51 g 100 g À1 , 1.26e2.48 g 100 g À1 and 5.57e5.61, respectively.…”
Section: Chemical and Physicochemical Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Spices are source of natural antioxidants and their effects on the formation of HCAs were investigated. Rosemary oleoresin [35], rosemary extract added to virgin olive oil [36], oleoresin or grape seed extract [37], spice-containing marinades [38], adding red and black pepper [39,40] can be effective inhibitors of HCAs formation. Marinating is another method can decrease the concentration of HCAs and several studies have shown reduced effect of marinated chicken before grilling on concentration of HCAs [41,42].…”
Section: +mentioning
confidence: 99%
“…The results have shown that pricklyash peel can inhibit HA formation, while star anise, fennel, cumin chili and black pepper promote HA formation. However, other studies have found that black and red pepper can significantly inhibit HA formation [17,18]. The results about the effects of spices on HA formation are controversial.…”
Section: Introductionmentioning
confidence: 95%